2017
DOI: 10.1111/adb.12521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N‐acetylcysteine on motivation, seeking and relapse to ethanol self‐administration

Abstract: Alcohol use disorder is a chronic and highly relapsing disorder, characterized by a loss of control over alcohol consumption and craving. Several studies suggest a key role of glutamate in this disorder. In recent years, the modulation of cystine/glutamate exchange via the x system has emerged as a new therapeutic alternative for reducing the excitatory glutamatergic transmission observed after ethanol self-administration in both rats and humans. The objective of this study was to determine whether a treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 59 publications
0
52
0
Order By: Relevance
“…In this regard, we recently used this BD model to show that N ‐acetylcysteine, which has been used off‐label to reduce craving in cocaine addiction, could also effectively reduce BD behavior (Lebourgeois et al . ). Thus indicating that our BD model has a good predictive validity.…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, we recently used this BD model to show that N ‐acetylcysteine, which has been used off‐label to reduce craving in cocaine addiction, could also effectively reduce BD behavior (Lebourgeois et al . ). Thus indicating that our BD model has a good predictive validity.…”
Section: Discussionmentioning
confidence: 97%
“…In well‐conducted studies, Lebourgeois and colleagues () showed that an i.p. of NAC (100 mg/kg) administered 60 minutes before operant‐cued relapse testing markedly inhibited EtOH relapse.…”
Section: Discussionmentioning
confidence: 99%
“…) and on ethanol seeking (Lebourgeois et al . ) could conceivably be explained by its anti‐inflammatory effects (Schneider et al . ).…”
Section: Discussionmentioning
confidence: 99%